LITERATUR REVIEW: IMPLEMENTASI KEBIJAKAN FLEKSIBILITAS WAKTU KERJA SEBAGAI STRATEGI PENGEMBANGAN SUMBER DAYA MANUSIA - Anis Malihatin; Eloh Bahiroh; Hilman Priyadi (Cahaya Ilmu Bangsa, 2025)
Working time flexibility policies are increasingly considered as one of the important strategies in human resource development in the dynamic era of globalisation. This literature review examines various studies related to the implementation of such policies and their impact on employee productivity, creativity, and mental health. The results show that working time flexibility can increase employee motivation and engagement, and support work-life balance. However, challenges in team coordination and performance evaluation remain key concerns in its implementation. In addition, information technology plays an important role in facilitating communication and collaboration between employees with diverse schedules. This policy not only contributes to employee skill development, but also strengthens the overall competitiveness of the organisation. This research provides recommendations for companies to integrate working time flexibility in HR management strategies to better achieve organisational goals.